Impact of childhood and adulthood psychological health on labour force participation and exit in later life. Issue 9 (15th February 2017) - Clark, C.; Smuk, M.; Lain, D.; Stansfeld, S. A.; Carr, E.; Head, J.; Vickerstaff, S.
Abstract : Background: Adulthood psychological health predicts labour force activity but few studies have examined childhood psychological health. We hypothesized that childhood psychological ill-health would be associated with labour force exit at 55 years. Method: Data were from the 55-year follow-up of the National Child Development Study ( n = 9137). Labour force participation and exit (unemployment, retirement, permanent sickness, homemaking/other) were self-reported at 55 years. Internalizing and externalizing problems in childhood (7, 11 and 16 years) and malaise in adulthood (23, 33, 42, 50 years) were assessed. Education, social class, periods of unemployment, partnership separations, number of children, and homemaking activity were measured throughout adulthood. Results: Childhood internalizing and externalizing problems were associated with unemployment, permanent sickness and homemaking/other at 55 years, after adjustment for adulthood psychological health and education: one or two reports of internalizing was associated with increased risk for unemployment [relative risk (RR) 1.59, 95% confidence interval (CI) 1.12–2.25; RR 2.37, 95% CI 1.48–3.79] and permanent sickness (RR 1.32, 95% CI 1.00–1.74; RR, 1.48, 95% CI 1.00–2.17); three reports of externalizing was associated with increased risk for unemployment (RR 2.26, 95% CI 1.01–5.04), permanent sickness (RR 2.63, 95% CI 1.46–4.73) and homemaking/other (RR 1.95, 95% CI 1.00–3.78). Conclusions: Psychological ill-health across the lifecourse, including during childhood, reduces the likelihood of working in older age. Support for those with mental health problems at different life stages and for those with limited connections to the labour market, including homemakers, is an essential dimension of attempts to extend working lives.